Cowards : what politicians, radicals, and the media refuse to say - Beck, Glenn (New York : Threshold Editions/Mercury Radio Arts, 2012)
This year, America will face one of the most important elections in history. But in the whirlwind of all the debates, attack ads, and super-PAC money, something that Americans used to hold in high regard has been lost: the truth. Glenn Beck believes that those who control the information--from the media to our politicians--are scared to tell the public the truth because of narrow, selfish interests, such as an impact on their ratings, or lobbying agendas, or re-election campaigns. People and organizations have agendas--but the truth does not. In Cowards, Beck provides his assessment of issues, ranging from border violence to Shariah law, from George Soros and the threat of economic terrorism to Frances Fox Piven and her strategy for collapsing our welfare system.--From publisher description.
Step right up! : the Progressive shell game -- The Libertarian option : ending the Progressive scam -- George Soros : the puppet master pulls all the strings -- Economic terrorism : financial weapons of mass destruction -- The American Dream is a lie -- Bordering on insanity : drugs, terrorists, and murder in our backyard -- The new police state : Big Brother is all grown up -- Jim Wallis and the attempted hijacking of religion -- Change the media, change the world -- The Islamist agenda : facts over fear -- Education : radical ideas to defeat the radicals -- Young socialists : why our kids think they hate capitalism -- Adapt on die : the coming intelligence explosion.
Includes bibliographical references (p. 272-306).
Keywords: United States -- Politics and government